An improved micromechanical model for the thermal conductivity of multi-scale fiber reinforced ultra-high performance concrete under high temperatures - Yao Zhang; Qianru Lei; Weigang Zhao; Yumeng Yang; Yichao Wang; Zhiguo Yan; Hehua Zhu; J. Woody Ju (Materials & Design, 2023)
An improved micromechanical model to estimate the thermal conductivity of multi-scale fiber reinforced ultra-high performance concrete (MSFUHPC) subjected to elevated temperatures is formulated in this study. This model considers the contributions of microstructure, multiscale fibers, water/cement ratio, thermal dehydration of hydrates, thermal cracking, interfacial thermal resistance, heating rate and temperature dependent thermal conductivity of each phase. To verify the proposed model, comparisons with experimental data on MSFUHPC specimens are carried out. Accordingly, factors affecting the thermal conductivity of MSFUHPC are discussed through the proposed model. Results suggest that blending multi-scale fibers and increasing the sand content can significantly enhance the thermal conductivity of MSFUHPC. While adding cenosphere particles can reduce the thermal conductivity. Overall, the thermal conductivity of MSFUHPC exhibits a decreasing trend with temperature. Meanwhile, thermal cracking occurs beyond 400 °C can remarkably decrease the thermal conductivity of MSFUHPC. A higher interfacial thermal resistance between sands and the matrix can result in a lower thermal conductivity. It is also found that thermal conductivity mainly depends on the maximum temperature experienced rather than the heating rate.